Teddy and Booker T. : [large type] how two American icons blazed a path for racial equality - Kilmeade, Brian (Random House Large Print, 2023)
When President Theodore Roosevelt welcomed the country's most visible Black man, Booker T. Washington, into his circle of counselors in 1901, the two confronted a shocking and violent wave of racist outrage. In the previous decade, Jim Crow laws had legalized discrimination in the South, eroding social and economic gains for former slaves. Lynching was on the rise, and Black Americans faced new barriers to voting. Slavery had been abolished, but if newly freed citizens were condemned to lives as share croppers, how much improvement would their lives really see? Brian Kilmeade tells the story of how two wildly different Americans faced the challenge of keeping America moving toward the promise of the Emancipation Proclamation. Theodore Roosevelt was white, born into incredible wealth and privilege in New York City. Booker T. Washington was Black, born on a plantation without even a last name. But both men embodied the rugged, pioneering spirit of America. Kilmeade takes us to San Juan Hill, where Roosevelt led his Rough Riders to a thrilling victory that set the stage for a legendary presidency, and to a small town in Alabama, where Washington founded the first university for African Americans, paving the way for the Civil Rights Movement. Both men abhorred the decadence and moral rot the nation had fallen into, believed that improvement through careful collaboration was possible, and trusted that the American ideals of individual liberty and hard work could propel the neediest toward success, if only those holding them back would step aside.